2003
DOI: 10.1093/hmg/ddg169
|View full text |Cite
|
Sign up to set email alerts
|

Selective striatal neuronal loss in a YAC128 mouse model of Huntington disease

Abstract: An expanded CAG repeat is the underlying genetic defect in Huntington disease, a disorder characterized by motor, psychiatric and cognitive deficits and striatal atrophy associated with neuronal loss. An accurate animal model of this disease is crucial for elucidation of the underlying natural history of the illness and also for testing experimental therapeutics. We established a new yeast artificial chromosome (YAC) mouse model of HD with the entire human HD gene containing 128 CAG repeats (YAC128) which deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

60
818
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 734 publications
(884 citation statements)
references
References 45 publications
60
818
6
Order By: Relevance
“…Weight loss, however, might also be an undesirable side effect of a specific treatment and needs to be reported when observed. As mentioned above, most of the full-length transgenic HD mouse models, such as BAC HD and YAC128, present significantly increased body weight (Gray et al, 2008;Slow et al, 2003), which has been found to negatively impact rotarod performance and locomotor activity assessments (body weight curves of the BAC HD line are shown in Figure 4). Consequently, the effects of treatments on the performance of BAC HD and YAC128 lines in these tests need to be considered in the context of their effects on body weight.…”
Section: Iii8 Body Weightmentioning
confidence: 90%
See 4 more Smart Citations
“…Weight loss, however, might also be an undesirable side effect of a specific treatment and needs to be reported when observed. As mentioned above, most of the full-length transgenic HD mouse models, such as BAC HD and YAC128, present significantly increased body weight (Gray et al, 2008;Slow et al, 2003), which has been found to negatively impact rotarod performance and locomotor activity assessments (body weight curves of the BAC HD line are shown in Figure 4). Consequently, the effects of treatments on the performance of BAC HD and YAC128 lines in these tests need to be considered in the context of their effects on body weight.…”
Section: Iii8 Body Weightmentioning
confidence: 90%
“…HD models in which the full-length HTT transgene is carried in either a yeast or a bacterial artificial chromosome (YAC and BAC, respectively) are also available (Hodgson et al, 1999;Slow et al, 2003;Gray et al, 2008); see Table 1. Unlike the shorter N-terminal fragment models, these larger transgenic constructs have a tendency to integrate into the genome at a single genomic locus and typically in low copy numbers (i.e., 1-3 transgene copies).…”
Section: I2 Full-length Transgenic Modelsmentioning
confidence: 99%
See 3 more Smart Citations